Trustworthy network based on blockchain technology - Cong LI; Bo LEI; Chongfeng XIE; Yunhe LI (Dianxin kexue)
With the frequent occurrence of network security issues,the industry had not satisfied the patch-based external security solution,and it was hoped that the endogenous security could be realized from the network architecture layer.The decentralized trustworthy network architecture was proposed.Based on the research of the security of existing network underlying protocol,a trustworthy network architecture based on decentralization technology was proposed,such as blockchain technology,which could effectively solve the problem of lack of endogenous security in existing networks.Layers implement network security to avoid malicious network attacks or network failures caused by configuration errors.